2018
DOI: 10.1186/s13099-018-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of genogroup II norovirus infections in acute gastroenteritis patients during 2014–2016 in Pudong New Area, Shanghai, China

Abstract: BackgroundNorovirus (NoV), a member of the Caliciviridae, is now recognized as the leading cause of acute gastroenteritis (AGE) worldwide. Globally, the GII.4 Sydney_2012 variant has predominated in NoV-related AGE since 2012, although the novel variant GII.17 has also been reported as responsible for gastroenteritis outbreaks in East Asia since 2014. This study aimed to disclose the recent genotype patterns of NoV genogroup II (GII) presenting in AGE patients in Pudong New Area of Shanghai through a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 36 publications
(39 reference statements)
4
34
0
Order By: Relevance
“…The oldest GII.3 NV strain identified to date is from a 1983 sample isolated in the Goulburn Valley of Australia [13], and GII.3 has been reported to be the major cause of sporadic pediatric NV infection [15,17,35,36]. In China, early reports on NV showed GII.3 was prevalent in 1999 [37,38], and until now, GII.3 was reported as the dominant genotype next to GII.4 in sporadic NV infection [39,40]. However, in this study, we found that NV GII.3 was the most prevalent strain among children hospitalized for AGE from 2012 to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…The oldest GII.3 NV strain identified to date is from a 1983 sample isolated in the Goulburn Valley of Australia [13], and GII.3 has been reported to be the major cause of sporadic pediatric NV infection [15,17,35,36]. In China, early reports on NV showed GII.3 was prevalent in 1999 [37,38], and until now, GII.3 was reported as the dominant genotype next to GII.4 in sporadic NV infection [39,40]. However, in this study, we found that NV GII.3 was the most prevalent strain among children hospitalized for AGE from 2012 to 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time reverse-transcription polymerase chain reaction (RT-PCR) was used for the initial sample testing for noroviruses according to the method we described previously 12 . VP1 sequences were further amplified from real-time RT-PCR-positive samples.…”
Section: Methodsmentioning
confidence: 99%
“…The fragment encoding VP1 was amplified and sequenced using the forward primer 5′-CNTGGGAGGGCGATCGCAA-3′ and reverse primer 5′-CCRCCNGCATRHCCRTTRTACAT-3′. The expected PCR product size was 343 bp 12 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in Shanghai mainly adopted either ORF1 or ORF2 nomenclature to understand the epidemiology of NoVs in children under five years of age [18][19][20][21][22]. Here, we adopted a dual nomenclature system based on both ORF1 and ORF2 to investigate the diversity of NoV GII genotypes in children suffering from acute gastroenteritis who visited the Children's Hospital of Fudan University in Shanghai from January 2012 to December 2017.…”
Section: Introductionmentioning
confidence: 99%